Plagioneurin B, a potent isolated compound induces apoptotic signalling pathways and cell cycle arrest in ovarian cancer cells - Nordin, Noraziah; Majid, Nazia Abdul; Othman, Rozana; Omer, Fatima Abdelmutaal Ahmed; Nasharuddin, Muhammad Nazil Afiq; Hashim, Najihah Mohd (Springer, 2018)
Plagioneurin B belongs to acetogenin group has well-established class of compounds. Acetogenin group has attracted worldwide attention in the past few years due their biological abilities as inhibitors for several types of tumour cells. Plagioneurin B was isolated via conventional chromatography and tested for thorough mechanistic apoptosis activity on human ovarian cancer cells (CAOV-3). Its structure was also docked at several possible targets using Autodock tools software. Our findings showed that plagioneurin B successfully inhibits the growth of CAOV-3 cells at IC 50 of 0.62 µM. The existence of apoptotic bodies, cell membrane blebbing and chromatin condensation indicated the hallmark of apoptosis. Increase of Annexin V-FITC bound to phosphatidylserine confirmed the apoptosis induction in the cells. The apoptosis event was triggered through the extrinsic and intrinsic pathways via activation of caspases 8 and 9, respectively. Stimulation of caspase 3 and the presence of DNA ladder suggested downstream apoptotic signalling were initiated. Further confirmation of apoptosis was conducted at the molecular levels where up-regulation in Bax, as well as down-regulation of Bcl-2, Hsp-70 and survivin were observed. Plagioneurin B was also seen to arrest CAOV-3 cells cycle at the G2/M phase. Docking simulation of plagioneurin B with CD95 demonstrated that the high binding affinity and hydrogen bonds formation may explain the capability of plagioneurin B to trigger apoptosis. This study is therefore importance in finding the effective compound that may offer an alternative drug for ovarian cancer treatment.